Modeling spatial variation in radiata pine slenderness (height/diameter ratio) and vulnerability to wind damage under current and future climate in New Zealand - Watt, Michael S.; Moore, John R. (Frontiers in Forests and Global Change, 2023)
Wind is a significant disturbance agent in forests that is likely to become more prevalent as plantation forests are increasingly grown at high stand density to maximise yields and carbon sequestration. Although research has used models to characterise plantation wind risk at discrete sites, little research has regionally scaled these predictions under both current and future climate. Stem slenderness, or height/diameter ratio, has been found to be a useful proxy for stand stability in the widely grown species, radiata pine (Pinus radiata), which constitutes 90% of the New Zealand plantation area. Stands with a slenderness that exceed 80 m m-1 are likely to be at risk when exposed to strong winds. In this study, slenderness was derived from 4,004 radiata pine permanent growth monitoring plots, that covered the spatial distribution of the species, and matched with stand density, age and key climatic and edaphic variables derived from surfaces. Using these data, the objectives of this study were to (i) develop a model to predict slenderness using machine learning and partition the impacts of key factors on slenderness, (ii) use this model to spatially predict slenderness throughout New Zealand for three contrasting silvicultural regimes, under current and future climate, and (iii) identify any regions that may be particularly vulnerable to wind risk. The final model of slenderness developed using the random forest algorithm included, in order of importance, stand density, stand age, mean annual air temperature and total annual rainfall. Predictions made on a withheld independent dataset (n = 401) were both unbiased and accurate (R2 = 0.85). Spatial predictions of slenderness under current climate showed wide regional variation with mean slenderness at age 30 years increasing from 62.1 m m-1 for low stand density clearwood regimes to 73.5 m m-1 for medium stand density structural grade regimes and 79.5 m m-1 for high stand density carbon regimes. Mean changes in slenderness were relatively low to 2040 and 2090 within the North Island. In contrast, within the South Island there were moderate increases in slenderness for the three silvicultural regimes that were markedly higher for 2090 than 2040.